2016
DOI: 10.1098/rsif.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the circularly polarized light reflection ofLomaptera(Scarabaeidae) beetles

Abstract: An extended spectroscopic study on the left-through-left circularly polarized reflection spectra of a large number of beetles from the Australasian Scrabaeidae:Cetoniinae of the Lomaptera genus was undertaken. We have obtained a five-category spectral classification. The principal spectral features, which even within the genus range from blue to infrared, are related to structural chirality in the beetle shells. The detailed features of each spectral classification are related to different structural perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…Beyond confirming the reflection of LCP light in two of the investigated specimens, the authors offered no additional insight into the CP behaviour exhibited by the beetles. The observation of CP reflected light for species belonging to the Lomaptera genus has been reported elsewhere, first by Neville & Caveney [37], and, more recently, by Carter et al [86], although, neither makes reference to the beetles' surface topography. Xu et al [85] presented a simplified model for the origin of the reflectance of the exocuticle structures revealed via TEM cross-sections, in which traditional multilayer reflectors, formed from alternating layers comprising distinct materials of high and low refractive index, were assumed.…”
Section: Optical Effect Of the Surface Topographymentioning
confidence: 73%
“…Beyond confirming the reflection of LCP light in two of the investigated specimens, the authors offered no additional insight into the CP behaviour exhibited by the beetles. The observation of CP reflected light for species belonging to the Lomaptera genus has been reported elsewhere, first by Neville & Caveney [37], and, more recently, by Carter et al [86], although, neither makes reference to the beetles' surface topography. Xu et al [85] presented a simplified model for the origin of the reflectance of the exocuticle structures revealed via TEM cross-sections, in which traditional multilayer reflectors, formed from alternating layers comprising distinct materials of high and low refractive index, were assumed.…”
Section: Optical Effect Of the Surface Topographymentioning
confidence: 73%
“…To obtain more information on the arrangement of the cellulose stack, we furthermore tried to use the classifications proposed by Carter et al for a non-ideal helicoidal reflector in beetles. The best matching classification is 'Spectra with diminishing oscillations', but such spectra are not well described by a few local defects or rsfs.royalsocietypublishing.org Interface Focus 9: 20180055 pitch changes, as described in their supplementary information [39]. Furthermore, looking at individual spectra from several cells (figure 5f ), we also found that no single classification fitted them all.…”
Section: Modelling the Optical Responsementioning
confidence: 83%
“…The model adopted so far to systematically analyse the optical response by helicoidal structures does not encompass all factors contributing to the spectral response. By trying to fit our spectra to the model developed to take into account defects and irregularities in spectra of helicoidal beetle cuticles [39], we were not able to reproduce all the measured spectral features. Therefore, we conclude that a few discrete defect sites do not dominate the reflection spectrum of the plant cell walls.…”
Section: Influence Of Disorder On Optical Responsementioning
confidence: 99%
“…Rigout and Allard (1997 : 88) treated L. d. viridipes as a variety of Lomaptera helleriana Valck Lucassen, 1961 without explanation. However, De Jong (1970 : 266) and Carter et al (2016 : 6) treated it as Lomaptera viridipes Moser, 1908.…”
Section: Resultsmentioning
confidence: 99%